Communication and management at work - Klikauer, Thomas (Palgrave Macmillan, 2007)
This book positions communication inside this historic development of work and management and shows how this development has led to the instrumental use of communication, informed by the distinction between those who manage and those who are managed and and directed towards the control and system integration of the workers